Modeled optical properties of SiGe and Si layers compared to spectroscopic ellipsometry measurements. (March 2017) - Kriso, C.; Triozon, F.; Delerue, C.; Schneider, L.; Abbate, F.; Nolot, E.; Rideau, D.; Niquet, Y.-M.; Mugny, G.; Tavernier, C.
Highlights: The optical response of Si and SiGe films is computed using a tight-binding approach. The calculations are compared with spectroscopic ellipsometry measurements. The influence of Ge concentration on the optical response is discussed. The influence of film thickness is attributed to quantum confinement effect. Abstract: The optical response of strained SiGe alloys, as well as thin Si layers, is analyzed using a sp 3 d 5 s ∗ tight-binding model within the independent particle approximation. The theoretical results are compared to measurements obtained on samples with various Ge content and layer thicknesses. The dielectric function is extracted from spectroscopic ellipsometry allowing a separation of its real and imaginary parts. Theory and simulation show similar trends for the variation of the dielectric function of SiGe with varying Ge content. Variations are also well reproduced for thin Si layers with varying thickness and are attributed to quantum confinement.